Fast Calculation of Material Radiation Damage by GPU Accelerated TRIM. (September 2020) - Qi, Meiling; Zhang, Yanshi; Duan, Jizheng; Chen, Xiaolong; Yang, Qiong; Yang, Lei
Abstract: An important function of TRIM is to research the radiation damage of ions implanted into materials. In this paper, GPU accelerated TRIM is developed for the fast calculation in study of material radiation bombarded by ions. The vacancies of iron induced by protons, alpha and carbon were simulated by GPU-TRIM. It reproduces the results well with SRIM2013. In the GPU test platform, TRIM achieves thousands of times the speed-up ratio.